Connections - Burke, James, 1936- (Boston : Little, Brown, 1978)
A companion to the PBS television series of the same name. Examines the ideas, inventions, and coincidences that have culminated in the major technological achievements of today.
Includes index.
Bibliography: p. 296-298.
Young Adult.
Young Adult
Keywords: Technology -- History; Technology -- History